Problems and countermeasures associated with intercultural adaptation in international education according to the communication action theory model - Liu, Yanjin; Song, Yun; Yan, Yun (Frontiers in Psychology, 2022)
Due to the development of the Chinese economy, the consolidation of national power worldwide, and the increasing frequency of economic and cultural exchanges with foreign countries, the number of people from various countries who travel to China to engage in exchanges has increased significantly. Given the development of economic globalization, the acceleration of the process of educational internationalization represents a general trend in higher education development and a common requirement for universities. In addition to education, international students also experience cross-cultural adaptation, that is, behavioral adaptation or changes that occur in people in response to changes in their home country, whether in the form of external or internal cultural adaptation. For international students, the problem of cross-cultural adaptation not only hinders their learning progress but also affects their psychology and living conditions. This article explains the construction of Habermas’s theory of communication action. According to this theory, the purpose of communication is to coordinate the common actions of actors, and this coordination is achieved through mutual communication, which is mediated by language. The article also discusses the cross-cultural adaptation experienced by international students in Chinese universities and highlights the importance of developing educational services for international students in the context of international education. Studies have shown that female students exhibit slightly worse psychological adaptation than male students and that female students have a slightly higher rate of depression rate than male students. An interpersonal study of 120 international students traveling to China found that most of these students (60%) were able to adapt in terms of their interpersonal relationships. To solve the problems associated with cross-cultural adaptation of international students in China, some countermeasures have been proposed, mainly including active participation in interpersonal communication, an enhanced understanding of the new culture, and the amplification of cultural identity.